Population contribution to polluting the city of Baghdad (Journal of the College of Basic Education, 2022)
The study aims at investigating population increasing in pollution in the capital city Baghdad Iraq. The pollution by Solid Wastes and Noise Pollution in particular.Questions at study: Is population growth in Baghdad the reason of Solid Wastes pollution? Is population growth in Baghdad the reason of Noise pollution? Are markets, stores and industrial workshops the main reason behind Solid Wastes pollution? Are markets, stores, industrial workshops, electricity generating machines, itinerant sellers and parties the main reason of Noise pollution?The questions were answered. During the answers using statistics in the years of conducting the study, it is found that: there is a big variation concerning Solid Wastes in terms of type and quantity. Noise Pollution raises highly in the regions that include many factors and industries. In addition, it is appeared that the main reason of pollution is the high population growth, which is 12.3 %. Due to the increase in birth rate, Economic development and the increase of spatial migration become of security.